#TITLE_ALTERNATIVE# - SETYA BUDHI, HARY
Along with the development of the era, causing many different type of human activity that need to be supported by the availability of adequate space. High rise building were built in order to fulfil the demand of space. However, Indonesia is a country that prone to earthquake, so in the building design, earthquake forces need to be considered. The higher the building, the drift due to the earthquake force will be greater. Therefore, engineers need to make a good planning in order to make an earthquake resistant building. Apartment Kebon Melati has the main function as a residential area. The apartment is located in Kebon Melati, Jakarta. The structure of the building consists 3 towers which have 28 floors, 30 floors, and 32 floors and 1 basement which serve as parking lot. The structural engineer must be able to translate the architectural design to structural design. In design stage, the structure must be designed in the most economical ways while keep the structure strong enough to bear the load due to building’s own load, dead loads and live loads. Especially in Indonesia, the structure must also be able to withstand earthquake load. Moreover, the structure is located in soft soil, so the building is categorized Seismic Design Category D (SDC-D). The structure is designed by using concrete as the main material and using dual system which are Special Moment Resisting Frame and Shear Wall as primary lateral resisting system. Based on the analysis, the structure’s period for each tower are 3,07 seconds, 3,83 seconds, and 3,57 seconds. The structure does not have horizontal irregularity and vertical irregularity. The structure also satisfies in story drift and P-Delta requirement. The upper and lower structure are analysed separately through a two-stage analysis. The seismic force from the upper structure is increased by 1,75 times. After the structural analysis is done, the design of the structural elements can be done. Detailing of structural elements refer to SNI 2847-2013 dan SNI 1727-2012. The structural elements that are designed are plates, beams, columns, shear walls, and coupling beam.